The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/bdra.20611
|View full text |Cite
|
Sign up to set email alerts
|

Pena‐Shokeir phenotype (Fetal akinesia deformation sequence) revisited

Abstract: Lack of fetal movement (fetal akinesia) in humans produces a recognizable sequence of deformations. Many developmental processes must be accomplished for fetal movement to be normal, and for extra-uterine life to be sustainable. Prenatal diagnosis is possible through real-time ultrasound studies as early as 12 weeks. Most reported cases die in utero, at birth, or in the newborn period. Advances in embryo/fetus pathology have led to the recognition of the many familial subtypes, allowing improved genetic counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
126
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 120 publications
1
126
0
Order By: Relevance
“…Skeletal muscle shows diffuse and group atrophy consistent with neurogenic atrophy. Often thin cerebral and cerebellar cortices with polymicrogyria are noted 3. Twin A in our study demonstrated most of these phenotypic findings, and a diagnosis of Pena–Shokeir syndrome was made.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Skeletal muscle shows diffuse and group atrophy consistent with neurogenic atrophy. Often thin cerebral and cerebellar cortices with polymicrogyria are noted 3. Twin A in our study demonstrated most of these phenotypic findings, and a diagnosis of Pena–Shokeir syndrome was made.…”
Section: Discussionsupporting
confidence: 55%
“…The classic features include intrauterine growth restriction, craniofacial anomalies, limb contractures, pulmonary hypoplasia, short umbilical cord, short gut, and pregnancy complications such as polyhydramnios, abnormal uterine positioning, and decreased fetal movements. Craniofacial abnormalities related to decreased fetal movements include ocular hypertelorism, high bridge of the nose, underdeveloped tip of the nose, posteriorly angulated ears that appear low‐set, short appearing neck with mild webbing, microretrognathia, high‐arched palate, and cleft palate 2, 3. Approximately 30% of affected children are stillborn.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not possible to discount the hypothesis that, in some cases, contractures could occur first and prevent normal movements, since contractures and (some form of) abnormality of movement are almost always identified together (Donker et al, 2009). Severely abnormal or absent foetal movements can result from muscular or neural conditions, such as myotonic dystrophy or central nervous system anomalies, restrictive dermopathy (a lethal autosomal recessive skin condition), teratogen exposure, intrauterine ischemia, or unknown causes (Hall, 2009;Witters et al, 2002;Yfantis et al, 2002). While restricted intrauterine space due to factors such as multiple pregnancy, uterine abnormalities or oligohydramnios, may reduce foetal movements, it is unlikely that space limitation alone will lead to the lethal form of FADS (Hall, 2009).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Focussing specifically on the skeleton, common symptoms include thin bones which are prone to fracture, clenched hands with adducted thumbs and scrambled fingers, congenital talipes equinovarus (club foot), and flexed or extended joint contractures (reviewed in Hall, 2009). Congenital kyphosis scoliosis and other spinal abnormalities have been reported (reviewed in Hall, 2009). Radiographic and histological analyses by Rodriguez et al (1998a) of eleven newborns who died due to complications arising from conditions of foetal immobility (due to spinal muscular atrophy, primary myopathic process and congenital myotonic dystrophy) revealed that the long bones were slender and hypomineralised.…”
Section: Foetal Akinesia Deformation Sequence (Fads)mentioning
confidence: 99%
See 1 more Smart Citation